Uncovering the Grylloidea and Tettigonioidea (Orthoptera: Ensifera) in the Forest Research Center (Sepilok) Entomological Collection - Tan, Ming Kai; Japir, Razy; Chung, Arthur Y.c. (Zootaxa, 2019)
Type specimens carry valuable information that can facilitate biodiversity research, especially in an era of mass extinction and unprecedent anthropogenic climate change. For Orthoptera, a few initiatives, including the Orthoptera Species File and digitization of collections by numerous museums, have helped to make images and information about the type specimens available on the World Wide Web. However, many local collections, especially those from the poorly studied regions of Southeast Asia, are still not available to the public. The collection of Grylloidea and Tettigonioidea gathered at the Forest Research Center, Sepilok in Sandakan, Sabah (Borneo) is one such example. We examined, identified, and imaged 12 and 45 species of Grylloidea and Tettigonioidea respectively from the collection (deposited as of October 2019) to facilitate taxonomic research by making the species in the collection accessible for everyone.